A zeolite activated carbon composite material and its preparation method and application
By modifying the surface of activated carbon, it is positively charged and combined with zeolite electrostatic attraction, the problems of low mechanical strength and insufficient adsorption performance of activated carbon-zeolite composites are solved, and efficient adsorption of volatile organic compounds is achieved.
Patent Information
- Application Number
- CN202310884213.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-07-18
AI Technical Summary
In the prior art, when preparing activated carbon-zeolite composites, the mechanical strength is low and the preparation process is complicated. The zeolite and activated carbon cannot be effectively combined, resulting in insufficient adsorption performance.
By using quaternary ammonium salt for modification of activated carbon surface, the charge of activated carbon is changed and positively charged, thereby avoiding electrostatic repulsion with negatively charged zeolites, and the electrostatic attraction combination between zeolite and modified activated carbon is achieved.
The high strength and high adsorption properties of zeolite activated carbon composites have been achieved, and the adsorption effect on volatile organic matter is significantly improved, far exceeding the performance of using activated carbon or zeolite alone.
Smart Images

Figure CN116726879B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of activated carbon modification, and specifically to a zeolite activated carbon composite material and a preparation method and application thereof. Background Art
[0002] The control and effective treatment of volatile organic compounds (VOCs) emissions have become the focus of the current global air pollution prevention and control. Among VOCs treatment technologies, the adsorption method has the advantages of mature technology, high purification efficiency, wide application range, and low energy consumption. It has been widely used either alone or in combination with other technologies. The core of adsorption purification technology is the adsorbent. Activated carbon and zeolite, as commonly used adsorbents in VOCs adsorption purification, each have unique advantages and also have insurmountable defects. VOCs come from a wide range of sources and types, including non-polar or weakly polar hydrocarbons and aromatic hydrocarbon compounds, as well as polar alcohols, aldehydes / ketones, fatty acids, and halogenated hydrocarbon compounds. The actual industrial source VOCs waste gas is often a mixture of multiple polar / non-polar organic matter. Although the use of zeolite and activated carbon segmented filling or segmented purification technology will solve the problem of adsorption purification of polar / non-polar mixed waste gas to a certain extent, the process is long and the equipment is complex. If activated carbon-zeolite molecular sieve composite adsorption materials can be prepared for VOCs purification, the problem of difficulty in adsorbing VOCs waste gas from industrial sources can be effectively solved.
[0003] The preparation of activated carbon and zeolite composite materials has been studied for a long time. From the early days, activated carbon and zeolite were mechanically mixed with a binder and then molded to obtain their composite materials. In recent years, agricultural and forestry wastes have been used to prepare zeolite / activated carbon composite materials, such as fly ash, coal gangue, wood fiber, etc. as raw materials, organic matter is converted into porous carbon after carbonization and activation, and inorganic matter is synthesized into zeolite by hydrothermal method. The problems with these methods are: the prepared composite materials have low mechanical strength and are easy to break; or the preparation process is complicated, involving carbonization, activation and crystallization, each stage is affected by different factors and mutually restricted; therefore, the structural control of the composite material is difficult to achieve. Rostami et al. proposed a method for preparing a composite material, that is, using activated carbon as a carrier, mixing it with a water glass solution, and then hydrothermally reacting it to obtain a zeolite activated carbon composite material. Although the preparation process is simple and fast, when the prepared samples were characterized, it was found that zeolite and activated carbon did not combine to form a composite material with the characteristics of both. In addition, there are many types of zeolites. Selecting which zeolite molecular sieve to match with activated carbon is the basis for preparing zeolite activated carbon composite materials for VOCs purification with broad spectrum and high efficiency. Summary of the invention
[0004] In view of the above-mentioned limitations, the present application proposes a zeolite activated carbon composite material; the surface of the activated carbon is modified by a quaternary ammonium salt to change the charge on the surface of the activated carbon, making it neutral or positively charged, thereby avoiding electrostatic repulsion with the negatively charged zeolite; when the surface of the modified activated carbon is positively charged, it can generate electrostatic attraction with the zeolite and thus combine with each other to form a zeolite activated carbon composite material, thereby overcoming the shortcomings and defects mentioned in the background technology.
[0005] To achieve the above objectives, this application adopts the following technical solutions:
[0006] The inventive point of the present application is to provide a zeolite activated carbon composite material, including modified activated carbon and zeolite; the modified activated carbon includes quaternary ammonium salt and activated carbon; the quaternary ammonium salt is located on the surface of the activated carbon; the zeolite is located on the surface of the modified activated carbon.
[0007] Optionally, the mass content of the zeolite in the zeolite-activated carbon composite material is ≥15%.
[0008] Optionally, the silicon to aluminum ratio of the zeolite is ≤30.
[0009] Optionally, the isocharge point of the modified activated carbon is ≥7; and the mass content of the quaternary ammonium salt in the modified activated carbon is 1% to 5%.
[0010] Another inventive point of the present application is to provide a method for preparing any of the zeolite activated carbon composite materials as described above.
[0011] Optionally, the preparation method comprises: (1) obtaining modified activated carbon; (2) mixing the modified activated carbon with a zeolite synthesis liquid, and crystallizing to obtain the zeolite activated carbon composite material; the zeolite synthesis liquid comprises a strongly alkaline hydroxide or an alkali metal oxide, a silicon source, an aluminum source, and water.
[0012] Optionally, step (1) comprises: mixing a quaternary ammonium salt solution with activated carbon, reacting, and obtaining modified activated carbon. Optionally, the amount of modified activated carbon added is 10-50wt% of the zeolite synthesis solution; and the crystallization conditions are: temperature 80-200°C, time ≥4h.
[0013] Optionally, step (2) comprises: mixing the modified activated carbon with a zeolite synthesis solution in the presence of zeolite seed crystals.
[0014] Optionally, zeolite seed crystals are dispersed in a solvent, and modified activated carbon is added to obtain a mixture I; and the mixture I is mixed with a zeolite synthesis liquid.
[0015] Another inventive point of the present application is to provide an application of any of the above-mentioned zeolite activated carbon composite materials in the process of adsorbing waste gas and wastewater, preferably in the adsorption of VOCs.
[0016] Compared with the prior art, this application has the following beneficial effects:
[0017] (1) In the zeolite activated carbon composite material of the present application, the modified activated carbon and zeolite are tightly combined and have high strength, and the zeolite content is high, most of which is located on the surface of the modified activated carbon, which can significantly improve the adsorption effect, which is far greater than the adsorption performance of activated carbon and zeolite when used alone. And the ignition point of the composite material is similar to that of activated carbon, that is, it will not reduce the thermal stability of the composite material.
[0018] (2) The present invention modifies the surface of activated carbon with quaternary ammonium salt, and through the electrostatic interaction between the positive charge of quaternary ammonium salt and the negative charge of activated carbon, the charge distribution on the surface of activated carbon is targeted to be changed, and at the same time, the carbon-carbon double bond or triple bond carried by the activated carbon is opened and bonded with the carbon on the surface of activated carbon to form a stable modified activated carbon. + The ions are located on the outside of the modified activated carbon, which ultimately changes the charged properties of the charge on the surface of the activated carbon, making it neutral or positively charged; the synthesis of zeolite is carried out under alkaline conditions, and activated carbon is negatively charged under alkaline conditions, and the activated carbon modified by quaternary ammonium salts is positively charged under alkaline conditions, and can attract negatively charged zeolite nuclei under electrostatic action, so that the nuclei are loaded on the surface of the activated carbon for further crystallization; when the surface of the modified activated carbon is positively charged, it can generate electrostatic attraction with the zeolite and thus combine with each other, and under the action of electrostatic attraction, a large number of zeolite nuclei are attracted to attach to the activated carbon, thereby improving the loading capacity and loading uniformity of the zeolite, and generating a zeolite-activated carbon composite material, which has a broad-spectrum characteristic of adsorbing VOCs. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a release curve of dimethyldiallylammonium chloride (DDA) in water in the modified activated carbon provided in one embodiment of the present application; the horizontal axis is time, the unit is h; the vertical axis is mass concentration, the unit is ppm. Figure 2 Microstructure diagrams of LTA zeolite and zeolite activated carbon composite material (LTA / D-AC) provided in one embodiment of the present application; (ac) zeolite activated carbon composite material (LTA / D-AC) prepared in Experimental Example 1; (d) XRD diagram of LTA zeolite generated by seed induction method, with the horizontal axis being 2θ, and the unit being °; the vertical axis being intensity, and having no unit; (ef) SEM and TEM images of LTA zeolite generated by seed induction method; (gi) SEM images of zeolite activated carbon composite material (LTA / D-AC) prepared in Experimental Example 2 at different angles.
[0020] Figure 3SEM images of zeolite activated carbon composite materials (LTA / D-AC) prepared by different methods provided in one embodiment of the present application; (a) and (b) are zeolite seeds dispersed in ethanol, activated carbon is added, and then added to the synthetic liquid; (c) and (d) are zeolite seeds added to the synthetic liquid before modified activated carbon; (e) and (f) are modified activated carbon added to the synthetic liquid before zeolite seeds.
[0021] Figure 4 Analytical diagram of the zeolite activated carbon composite material (LTA / D-AC) provided in one embodiment of the present application; (a) and (b) are microscopic morphology diagrams of the composite material; (c) and (d) are element distribution diagrams of the composite material.
[0022] Figure 5 Analytical diagram of the zeolite activated carbon composite material provided in Test Example 6 of the present application; (a) is the XRD diagram of the zeolite activated carbon composite material, the horizontal axis is 2θ, the unit is °; the vertical axis is intensity, without unit; (b) is the SEM diagram of the zeolite activated carbon composite material.
[0023] Figure 6 Analytical diagrams of the ZSM-5 zeolite and zeolite activated carbon composite material (ZSM-5 / D-AC) provided in one embodiment of the present application; (a) is the XRD of the ZSM-5 zeolite, the abscissa is 2θ, the unit is °; the ordinate is intensity, without unit; (b) is the SEM image of the ZSM-5 zeolite; (c) is the TEM image of the ZSM-5 zeolite; (df) are SEM images of ZSM-5 / D-AC at different angles.
[0024] Figure 7 (a) is a simulation process diagram of the combination of LTA zeolite and modified activated carbon (D-AC) provided in one embodiment of the present application; Figure 7 (b) SEM images of the reaction products of activated carbon (AC) and LTA zeolite at different angles. Figure 8 (a) is the adsorption performance diagram of dichloromethane by zeolite activated carbon composite material (LTA / D-AC); the horizontal axis is time, unit min; the vertical axis is C t / C0, unitless; Figure 8 (b) Adsorption capacity of zeolite activated carbon composite material (LTA / D-AC), LTA zeolite, and activated carbon; the horizontal axis is relative pressure P / P0, no unit; the vertical axis is adsorption capacity, unit is cm 3 / g.
[0025] Fig. 9 The weight loss curves of activated carbon (a) and zeolite activated carbon composite material LTA / D-AC (b); the abscissa is temperature, in °C; the ordinate is mass, in %.
[0026] Fig.10TEM images of composite material 1 in Example 4; (a) 50 μm; (b) 20 μm; (c) 10 μm; (d) 2 μm.
[0027] Fig.11 TEM images of composite material 2 in Example 4; (a) 50 μm; (b) 20 μm; (c) 10 μm; (d) 2 μm.
[0028] Fig.12 The nitrogen adsorption and desorption test diagram of the columnar carbon, composite material 1 and composite material 2 in Example 4; the horizontal axis is the columnar carbon, composite material 1 and composite material 2; the vertical axis is the surface area, the unit is m 2 / g. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below. However, it should be understood that the description here is only used to explain the present application and is not used to limit the scope of the present application.
[0030] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present application, and the terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The reagents and instruments used herein are all commercially available, and the characterization means involved can refer to the relevant descriptions in the prior art, which will not be repeated herein.
[0031] In order to further understand the present application, the present application is further described in detail below in conjunction with the best embodiment.
[0032] Example 1
[0033] This embodiment provides a zeolite activated carbon composite material, including modified activated carbon and zeolite; the modified activated carbon includes quaternary ammonium salt and activated carbon; the quaternary ammonium salt is located on the surface of the activated carbon; the zeolite is located on the surface of the modified activated carbon.
[0034] When the quaternary ammonium salt is loaded on the surface of activated carbon through chemical bonding between the quaternary ammonium salt and the activated carbon, the quaternary ammonium salt is targeted to the surface of activated carbon through the electrostatic interaction between the positive charge of the quaternary ammonium salt and the negative charge of the activated carbon. At the same time, the carbon-carbon double or triple bond carried by the quaternary ammonium salt is opened and bonded with the carbon on the surface of the activated carbon to form a stable modified activated carbon. + The ions are located on the outside of the modified activated carbon.
[0035] For the modified activated carbon after the surface modification of activated carbon, its surface carries positive charge, which attracts the negatively charged zeolite nuclei under the action of electrostatic attraction, so that the nuclei are loaded on the surface of activated carbon for further crystallization, and finally a large amount of zeolite is attached to the activated carbon, thereby improving the loading capacity and loading uniformity of activated carbon for zeolite.
[0036] The mass content of zeolite in the zeolite activated carbon composite material is ≥15%.
[0037] When the mass content of zeolite is less than 15%, it is considered that zeolite and activated carbon do not form a composite material; preferably, the mass content is ≥20%. The zeolite content in the zeolite activated carbon composite material prepared in the present application is above 15%. The silicon-aluminum ratio of the zeolite is ≤30.
[0038] Zeolite is a tetrahedral structure composed of silicon oxygen and aluminum oxygen. Among them, the outermost layer of silicon atoms has 4 electrons, 1 silicon atom is bonded with 4 oxygen atoms, and the system charge is balanced, while the outermost layer of aluminum atoms has 3 electrons, and 1 aluminum atom is bonded with 4 oxygen atoms to form a tetrahedron, resulting in a negative charge in the system. Therefore, the higher the aluminum atom content in the zeolite, the stronger the negative charge of the zeolite. Conversely, the lower the aluminum content in the zeolite, the weaker the negative charge of the zeolite. Therefore, when the silicon content in the zeolite is too high, that is, when the silicon-aluminum ratio is large, the negative charge of the zeolite will be weakened, or even neutral, and it will be difficult to combine with the positively charged modified activated carbon through electrostatic force; when the silicon-aluminum ratio is small, the zeolite will be negatively charged and can be loaded on the surface of the modified activated carbon through electrostatic force interaction. Therefore, the silicon-aluminum ratio is ≤30, preferably the silicon-aluminum ratio is ≤20, preferably ≤15, more preferably ≤10, and more preferably ≤5.
[0039] The above-mentioned zeolite can be selected from natural or artificially synthesized zeolites with low silicon-to-aluminum ratio, or low-silicon zeolites can be loaded and then dealuminated to increase the silicon-to-aluminum ratio of the loaded zeolite.
[0040] The isoelectric point of the modified activated carbon is ≥7; the mass content of the quaternary ammonium salt in the modified activated carbon is 1% to 5%.
[0041] Only when the isocharge point of the modified activated carbon is ≥7, it indicates that the charge distribution on the surface of the activated carbon has changed from negative charge to neutral or positive charge.
[0042] The quaternary ammonium salt is selected from at least one of the compounds having the structure of formula II,
[0043]
[0044] Among them, X -It is an ion with a negative charge; R1, R2, R3, and R4 are independently selected from any one of C1-C5 alkanes, alkenes, or alkynes with or without substituents; at least one of R1, R2, R3, and R4 contains a carbon-carbon double bond or a carbon-carbon triple bond.
[0045] X is a halogen, selected from any one of F, Cl, Br, I and At.
[0046] The quaternary ammonium salt is selected from at least one of the compounds having the structure of formula III,
[0047]
[0048] Among them, R1, R2, R3, and R4 are independently selected from any one of C1-C5 alkanes, alkenes, or alkynes with or without substituents; at least one of R1, R2, R3, and R4 contains a carbon-carbon double bond or a carbon-carbon triple bond.
[0049] The quaternary ammonium salt is selected from at least one of the compounds having the structure of formula IV,
[0050]
[0051] Among them, X - is an ion with a negative charge; R 11 , R 21 Any one independently selected from C1-C4 alkanes, alkenes or alkynes which may or may not have a substituent.
[0052] The quaternary ammonium salt is selected from at least one compound having a structure of formula V,
[0053]
[0054] Among them, R 11 , R 21 Any one independently selected from C1-C4 alkanes, alkenes or alkynes which may or may not have a substituent.
[0055] The quaternary ammonium salt is dimethyldiallylammonium chloride, and the structural formula is:
[0056]
[0057] The carbon-carbon double bonds or carbon-carbon triple bonds in the quaternary ammonium salt are combined with the carbon on the surface of the activated carbon.
[0058] The mass content of the quaternary ammonium salt in the modified activated carbon is 1% to 5%.
[0059] The quaternary ammonium salt first reacts with the carbon on the surface of the activated carbon to generate a stable carbon-carbon single bond. However, as the amount of the quaternary ammonium salt increases, after the activated carbon surface reacts with the quaternary ammonium salt, that is, when the quaternary ammonium salt has covered most of the activated carbon surface, due to steric hindrance, it is difficult for the surface to react again, and too much quaternary ammonium salt will enter the pores and react with the carbon in the pores, thereby causing pore blockage. The present application can avoid pore blockage to a certain extent by controlling the proportion of quaternary ammonium salt in the entire modified activated carbon, and achieves the effect of only changing the surface charge of the activated carbon.
[0060] Example 2
[0061] This embodiment provides a method for preparing a zeolite activated carbon composite material. The zeolite activated carbon composite material is the same as the zeolite activated carbon composite material described in Example 1, and will not be described in detail here.
[0062] The preparation method comprises: (1) obtaining modified activated carbon; (2) mixing the modified activated carbon with zeolite synthesis liquid, crystallizing, and obtaining the zeolite activated carbon composite material; the zeolite synthesis liquid comprises a strong alkaline hydroxide or a mixed alkali, a silicon source, an aluminum source, and water.
[0063] Step (1) comprises: mixing a quaternary ammonium salt solution with activated carbon, reacting the mixture, and obtaining modified activated carbon.
[0064] The carbon-carbon double bonds or carbon-carbon triple bonds in the quaternary ammonium salt are combined with the carbon on the surface of the activated carbon.
[0065] Prepare a 5wt% dimethyldiallyl ammonium chloride solution (solvent is water), according to the solid-liquid ratio of 1g (activated carbon sample): 50ml (dimethyldiallyl ammonium chloride solution), take a certain amount of activated carbon sample and dimethyldiallyl ammonium chloride solution and add them into a conical flask, and place the conical flask at room temperature (25°C) for water bath oscillation (160rpm / min) for 3h; filter the mixed solution, and place the solid sample obtained by filtration in an oven at 80°C for drying for 12h to obtain modified activated carbon. The amount of modified activated carbon added is 10-50wt% of the zeolite synthesis solution, for example, it can be 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt% or 50wt%.
[0066] The crystallization conditions are: temperature 80-200°C, time ≥4h.
[0067] The temperature of crystallization may be 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C.
[0068] The crystallization time may be 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h or more.
[0069] When the synthesis of zeolite is relatively simple, the modified activated carbon can be directly mixed with the zeolite synthesis liquid for crystallization; if the synthesis of zeolite is relatively complex and requires the use of seed crystals or templates, the modified activated carbon needs to be mixed with the zeolite synthesis liquid in the presence of zeolite seed crystals. When both methods are available, you can choose according to the actual situation.
[0070] The mass ratio of zeolite synthesis liquid to zeolite seed crystals is 100:(0.1-2).
[0071] The zeolite seed crystals are dispersed in a solvent, and modified activated carbon is added to obtain a mixture I; and the mixture I is mixed with a zeolite synthesis liquid.
[0072] The seed crystals are added to ethanol, and ultrasonic waves are used to evenly disperse them in the ethanol, and then modified activated carbon is added to effectively combine with the seed crystals. After a period of time, the ethanol is dried to remove the modified activated carbon combined with the seed crystals, and then added to the synthetic liquid to prepare the zeolite activated carbon composite material.
[0073] Since the seed crystals are generally small in size and the activated carbon is also small in size, they are easy to agglomerate and agglomerate when added directly to the synthetic liquid; this affects the combination of the two, resulting in uneven zeolite loading on the surface of the activated carbon. Moreover, the combination process of the seed crystals and the activated carbon takes time. When they are added to the synthetic liquid at the same time, the seeds surrounded by the silicon source and the aluminum source may crystallize first, which also affects their combination. Therefore, the seed crystals can be dispersed in the solvent first, and then the modified activated carbon can be added to disperse them on the surface of the modified activated carbon, reducing the agglomeration between the seed crystals and the activated carbon, and promoting the seed crystals and the activated carbon to combine with each other through electrostatic interaction, laying a good foundation for subsequent crystallization, and avoiding problems such as uneven loading.
[0074] The synthetic liquid is any synthetic liquid required for conventional zeolite, generally including a strong alkaline hydroxide or mixed alkali, a silicon source, an aluminum source, and water, and can be used for the synthesis of zeolite. It can be any strong alkaline hydroxide or mixed alkali, silicon source, and aluminum source commonly used on the market, and is not limited to this. The molar ratio between the strong alkaline hydroxide or mixed alkali, silicon source, aluminum source, and water can also be selected according to conventional methods.
[0075] Example 3
[0076] According to the content of this application, the zeolite activated carbon composite material of Example 1 and the preparation method of Example 2 are specifically described, and the specific description is as follows:
[0077] Diallyldimethylammonium chloride (DDA, 60wt%), silica sol (29-31wt%), sodium aluminate (AR grade), aluminum sulfate (AR grade), tetrapropylammonium hydroxide (TPAOH, AR grade), tetraethyl orthosilicate (TEOS, 25wt%), and sodium hydroxide (AR grade) were purchased from Shanghai McLean Biochemical Co., Ltd.
[0078] LTA zeolite powder was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and 5A zeolite powder.
[0079] Activated carbon: The commercial columnar activated carbon produced by Ningxia Wangdakai Coal Industry Co., Ltd. was ground in a mill to a particle size of less than 74 μm and then air-dried to constant weight.
[0080] Preparation method of modified activated carbon:
[0081] Prepare a 5wt% dimethyldiallyl ammonium chloride solution (solvent is water), according to the solid-liquid ratio of 1g (activated carbon, AC): 50ml (dimethyldiallyl ammonium chloride solution), take a certain amount of activated carbon sample and dimethyldiallyl ammonium chloride solution and add them into a conical flask, and place the conical flask at room temperature (25°C) for water bath oscillation (160rpm / min) for 3h; filter the mixed solution, and place the solid sample obtained by filtration in an oven at 80°C for drying for 12h to obtain modified activated carbon (the mass content of quaternary ammonium salt in the modified activated carbon is 10wt%). The modified activated carbon is positively charged in an alkaline solution (pH>7), that is, the isoelectric point of the modified activated carbon is ≥7.
[0082] Since the synthesis of zeolite takes a long time, it is necessary to verify whether dimethyldiallylammonium chloride (DDA) can be tightly combined with activated carbon for a long time to ensure that the zeolite is effectively attracted to the surface of the modified activated carbon during the synthesis process.
[0083] The combination of dimethyldiallylammonium chloride (DDA) and activated carbon (AC) can be verified by the following method: the modified activated carbon (D-AC) and deionized water are mixed in a conical flask at a solid-liquid ratio of 1:500 g / mL, and the conical flask is placed in a water bath shaker at a frequency of 150 r / min and a temperature of 25 ° C. The vibration is continued for 24 hours, and the vibration is stopped. Samples are collected every 2 hours to determine the concentration of dimethyldiallylammonium chloride (DDA) in the filtrate. The determination of dimethyldiallylammonium chloride (DDA) in water is relatively complicated because it cannot be determined by UV-visible spectrophotometry. The content of dimethyldiallylammonium chloride (DDA) in water is determined by the working curve method of indirect capillary electrophoresis (Beckman Coulter, P / ACETM MDQCE), the detector is 200nm UV, the buffer solution is an acetic acid-imidazole system, and the separation voltage is 20kV.
[0084] Considering that zeolite synthesis takes a long time, whether the dimethyldiallyl ammonium chloride (DDA) molecules will separate from the surface of activated carbon (AC), resulting in a weak attraction to zeolite loading. Therefore, it is necessary to verify the binding strength of dimethyldiallyl ammonium chloride (DDA) and activated carbon (AC) in the solution for a long time. The results of the shake flask experiment are shown in Figure 1 .
[0085] like Figure 1 As shown in the figure, during the 2h shake flask experiment, the DDA molecules were easily separated from the surface of the modified activated carbon (D-AC) and released into the water, resulting in a DDA concentration in the water exceeding 300ppm. However, as the experiment continued, the DDA content in the water decreased significantly and was less than 100ppm after 24 hours. Previous work has pointed out that the C=C bond in DDA reacts with the phenolic hydroxyl groups on the activated carbon (AC). It can be inferred that as time increases, these released DDA molecules will react with the phenolic hydroxyl groups on the activated carbon (AC) and then be fixed on the AC. In addition, the activated carbon (AC) with a well-developed pore structure also has an adsorption capacity for DDA molecules, and some of the released DDA molecules are adsorbed into the pores. The results showed that as the experimental time increased, the amount of dimethyldiallylammonium chloride (DDA) released into water from the modified activated carbon (D-AC) became less and less. It can be concluded that the long time required for the synthesis of zeolite did not lead to a large release of dimethyldiallylammonium chloride (DDA) from the modified activated carbon (D-AC), but rather promoted their better binding.
[0086] Quaternary ammonium salts are often used as cationic surfactants to modify porous materials to improve the adsorption capacity of porous materials for anionic pollutants in water. From the modification effect, the modification can effectively improve the Zeta potential of the material. IEP ) is the point at which the Zeta potential is zero. There is ample evidence that pH IEP It can reflect the external electrical properties of the modified material in different water environments. Studies have found that dimethyldiallyl ammonium chloride (DDA) can change the pH of activated carbon (AC) IEPIt significantly increased to more than 12, indicating that the modified activated carbon (D-AC) has a positive charge in alkaline solution. This means that dimethyldiallyl ammonium chloride (DDA) is attached to the surface of activated carbon (AC), changing the charge distribution on the surface of activated carbon (AC). At the same time, the charge distribution of modified activated carbon (D-AC) modified by dimethyldiallyl ammonium chloride (DDA) has little negative impact on its original pore structure, which is much lower than other types of quaternary ammonium salts such as benzalkonium chloride and QUAB series used in various reports.
[0087] Test Example 1
[0088] The modified activated carbon was added to a zeolite synthesis solution (the molar ratio of Na2O:Al2O3:SiO2:H2O was 3.165:1:1.926:128), then aged at room temperature for 24 hours, transferred to a hydrothermal reactor, and placed in an oven for heating and crystallization. The crystallization temperature was 100°C and the crystallization time was 4 hours. After washing, filtering and drying, a zeolite activated carbon composite material (LTA / D-AC) was obtained. The amount of the modified activated carbon added was 10wt% of the zeolite synthesis solution. The silicon-aluminum ratio of the zeolite was 2:1.926; the mass content of the zeolite in the zeolite activated carbon composite material was 37.16%.
[0089] like Figure 2 (a)- Figure 2 As shown in (c), a certain amount of LTA zeolite is loaded on the modified activated carbon. However, the LTA zeolite is not uniformly loaded on the surface of the modified activated carbon, especially the zeolite loaded on the smooth surface of the modified activated carbon, which is sparsely distributed. It is speculated that low-silicon zeolite has a higher negative charge and can combine with the positively charged modified activated carbon in the solution, but zeolite crystal growth is the main reaction in the system, and the process of zeolite combining with modified activated carbon is weak and needs to be further strengthened.
[0090] Test Example 2
[0091] The seed induction method was used to optimize the loading of LTA zeolite on activated carbon by artificially enhancing the bonding process between LTA zeolite and activated carbon.
[0092] First, we verified whether LTA zeolite could be generated by the seed induction method.
[0093] The specific process of the test is as follows:
[0094] LTA zeolite powder was used as zeolite seed crystals; a synthetic liquid (the molar ratio of Na2O:Al2O3:SiO2:H2O was 3.165:1:1.926:128) was prepared, the synthetic liquid and the zeolite seed crystals were fully mixed, and then after aging at room temperature for 24 hours, the synthetic liquid was transferred to a hydrothermal reactor and placed in an oven for heating and crystallization, the crystallization temperature was 100°C, the crystallization time was 6 hours, and the LTA zeolite was obtained after washing, filtering and drying. Among them, the mass ratio of the zeolite synthetic liquid to the zeolite seed crystals was 100:0.6.
[0095] The product was measured to verify whether this method can synthesize LTA zeolite. Figure 2 (d)- Figure 2 As shown in (f), the product has the characteristic diffraction peaks and cubic morphology of LTA zeolite, indicating that the seed induction method is also suitable for the preparation of LTA zeolite.
[0096] On the basis of the above, the seeds and modified activated carbon were added to the synthetic liquid at the same time to prepare the composite material. The specific process is as follows:
[0097] LTA zeolite powder was used as zeolite seed; a synthetic liquid (Na2O:Al2O3:SiO2:H2O molar ratio was 3.165:1:1.926:128) was prepared, the synthetic liquid, zeolite seed and modified activated carbon were fully mixed, then added to a stainless steel autoclave for aging at room temperature for 24 hours and then placed in an oven, the crystallization temperature was 100°C, the crystallization time was 4 hours, and a zeolite activated carbon composite material (LTA / D-AC) was obtained after washing, filtering and drying. Among them, the mass ratio of zeolite synthetic liquid to zeolite seed was 100:0.6; the amount of modified activated carbon added was 10wt% of the zeolite synthetic liquid. The silicon-aluminum ratio of the zeolite was 1:1; the mass content of zeolite in the zeolite activated carbon composite material was 46.51%.
[0098] The product was tested and the results were as follows Figure 2 (g)- Figure 2 As shown in (i), the composite material prepared by this method further increases the loading of zeolite on the surface of modified activated carbon. In addition, compared with the zeolite directly synthesized by the seed induction method, the zeolite is mostly cubic. After adding modified activated carbon, the amount of cubic zeolite loaded on the surface of modified activated carbon is significantly reduced, indicating that the modified activated carbon affects the growth process of LTA zeolite.
[0099] Test Example 3
[0100] Using LTA zeolite powder as zeolite seed;
[0101] The zeolite seed crystals are added to ethanol, and ultrasonic waves are used to uniformly disperse the zeolite seed crystals in the ethanol, and then the modified activated carbon is added; after a period of time, the ethanol is removed by drying to obtain the modified activated carbon combined with the seed crystals;
[0102] The modified activated carbon combined with the seed crystal was added to the zeolite synthesis liquid (the molar ratio of Na2O:Al2O3:SiO2:H2O was 3.165:1:1.926:128), and then transferred to a hydrothermal reactor after aging at room temperature for 24 hours, and placed in an oven for heating and crystallization. The crystallization temperature was 100°C and the crystallization time was 4 hours. After washing, filtering and drying, a zeolite activated carbon composite material (LTA / D-AC) was obtained. Among them, the mass ratio of zeolite synthesis liquid to zeolite seed crystal was 100:0.6; the amount of modified activated carbon added was 10wt% of the zeolite synthesis liquid.
[0103] Low-silicon zeolite with high aluminum content has strong negative electrical properties. The LTA zeolite in this test example has a high aluminum content and an aluminum-silicon ratio close to 1:1. It has good negative electrical properties and can be combined with positively charged modified activated carbon to form a composite material. The mass content of zeolite in the zeolite-activated carbon composite material is 58.20%.
[0104] The results are as follows Figure 3 As shown, from Figure 3 (a) and Figure 3 As can be seen in (b), the agglomeration of seeds and modified activated carbon was resolved by using ethanol solution and ultrasonic dispersion, and the two were fully combined by electrostatic attraction. The seeds were evenly distributed on the surface of the modified activated carbon, and a satisfactory zeolite activated carbon composite material (LTA / D-AC) was obtained after crystallization, that is, a large amount of LTA zeolite was loaded on the modified activated carbon.
[0105] Test Example 4
[0106] It is similar to Experimental Example 3, except that the order of addition is changed: the modified activated carbon is added to the synthetic liquid first, and then the zeolite seeds are added; or the zeolite seeds are added to the synthetic liquid first, and then the modified activated carbon is added. Figure 3 (c)- Figure 3 As shown in (f), regardless of whether the seeds or AC are added to the synthesis solution in sequence, the loading of LTA zeolite on the modified activated carbon in the prepared composite material is significantly weaker, and the mass content of zeolite in the zeolite-activated carbon composite material is 47.2% and 47.38%, respectively.
[0107] Test Example 5
[0108] It is similar to Experimental Example 3, except that the crystallization time is changed to 12 hours. The other conditions are the same as Experimental Example 3, and a zeolite activated carbon composite material is obtained; wherein the mass content of zeolite in the zeolite activated carbon composite material is 62.46%.
[0109] Growth results in composite materials such as Figure 4 (a) and Figure 4 As shown in (b), due to the increase in crystallization time, the zeolites loaded on the surface of the modified activated carbon become more and more dense, and the number of zeolites with regular shapes also increases.
[0110] In order to verify that the prepared samples are LTA / D-AC composites, Figure 4 (b) The element distribution on the sample surface was analyzed by EDS, such as Figure 4 (c) and Figure 4 (d). The results show that there are a large amount of silicon and aluminum elements on the surface of the sample, and the ratio is close to 1:1, which is similar to LTA zeolite. In addition, there is a large amount of carbon under the silicon and aluminum, which proves that LTA zeolite is loaded on the surface of modified activated carbon. In summary, ethanol and ultrasonic dispersion can be used to eliminate the agglomeration of seeds and modified activated carbon powders, so that they are combined with each other through electrostatic attraction, and then the low-silicon zeolite composite material loaded on the surface of modified activated carbon is successfully prepared by prolonging the crystallization time.
[0111] Test Example 6
[0112] Using 13X zeolite powder as zeolite seed crystals;
[0113] Zeolite seed crystals are added to ethanol, and ultrasonic waves are used to uniformly disperse the zeolite seed crystals in the ethanol, and then modified activated carbon is added; after a period of time, the ethanol is removed by drying to obtain modified activated carbon combined with the seed crystals.
[0114] The modified activated carbon combined with the seed crystal was added to the zeolite synthesis liquid (the molar ratio of Na2O:K2O:Al2O3:SiO2:H2O was 5.5:1.65:1:2.2:122), and then the reaction liquid was poured into a polytetrafluoroethylene liner and aged at 70°C for 3 hours, then transferred to a hydrothermal reactor and placed in an oven for heating and crystallization. The crystallization temperature was 100°C and the crystallization time was 2 hours. Finally, after washing, filtering and drying, a zeolite activated carbon composite material (13X / D-AC) was obtained. Among them, the mass ratio of zeolite synthesis liquid to zeolite seed crystal was 100:0.6; the amount of modified activated carbon added was 10wt% of the zeolite synthesis liquid. The silicon-aluminum ratio of the zeolite was 1.1:1; and the mass content of zeolite in the zeolite activated carbon composite material was 50.51%.
[0115] The product was tested and the results were as follows Figure 5 As shown by Figure 5 (a) It can be seen that the product has the characteristic diffraction peaks of 13X zeolite, indicating that the seed induction method is also applicable to 13X zeolite. Figure 5 (b) shows that 13X zeolite can be successfully loaded on the surface of modified activated carbon.
[0116] Comparative Example 1
[0117] Preparation of zeolite seed crystals: a zeolite precursor suspension with a molar ratio of TEOS:TPAOH:H2O of 1:0.36:19.2 was prepared, transferred to a hydrothermal reactor, crystallized in an oven at 100°C for 24h, centrifugally dried, and calcined at 550°C for 6h to obtain zeolite seed crystals;
[0118] A synthetic solution (Na2O:Al2O3:SiO2:H2O in a molar ratio of 12:2:100:2500) was prepared, the synthetic solution and zeolite seed crystals were fully mixed in a mass ratio of 100:1, then added to a stainless steel autoclave for aging at room temperature for 24 hours, then placed in an oven for crystallization at 180°C for 24 hours, and washed, filtered, and dried to obtain ZSM-5 zeolite;
[0119] A synthetic solution (the molar ratio of Na2O:Al2O3:SiO2:H2O is 12:2:100:2500) was prepared, and the synthetic solution, zeolite seeds and modified activated carbon were fully mixed in a mass ratio of 100:0.6:10. The mixture was then added to a stainless steel high-pressure sterilizer and aged at room temperature for 24 h. The mixture was then placed in an oven and crystallized at 180°C for 24 h. The zeolite activated carbon composite material (ZSM-5 / D-AC) was obtained after washing, filtering and drying.
[0120] Since high-silicon zeolite has good hydrophobicity, strong dispersibility and electrostatic force, it has good adsorption capacity for highly polar molecules. Therefore, the introduction of high-silicon zeolite on D-AC is beneficial to improving the adsorption effect of the composite material on polar VOCs. At the same time, the increase in silicon content in the composite material can effectively improve its flame retardancy. ZSM-5 zeolite, as a typical high-silicon MFI zeolite, has a wide range of applications in adsorption, catalysis and other fields. The ZSM-5 zeolite and zeolite activated carbon composite material (ZSM-5 / D-AC) obtained by the above preparation method were characterized, and the results are shown in Figure 2. Figure 6 .
[0121] from Figure 6 (a) It can be seen that the product has obvious characteristic diffraction peaks of ZSM-5 zeolite. Figure 6 (b) and Figure 6 (c) It can also be seen that the microscopic morphology of the product is coffin-shaped, which confirms that this method can successfully synthesize ZSM-5 zeolite.
[0122] The SEM results of zeolite activated carbon composite material (ZSM-5 / D-AC) are as follows Figure 6 The results show that only a small amount of ZSM-5 zeolite is loaded on the surface of AC, and the mass content of zeolite in the zeolite activated carbon composite material is only about 12.51%, which is consistent with the results of previous studies, that is, AC and zeolite are independent of each other and do not form an integral structure, which indicates that ZSM-5 zeolite and modified AC cannot be combined under the induction of electrostatic attraction.
[0123] The above experiments confirmed that the surface charge of AC was modified by quaternary ammonium salt, so that it was positively charged in a strong alkaline solution and self-assembled with negatively charged low-silicon zeolite through electrostatic attraction. In order to verify this inference that quaternary ammonium salt improves the surface of activated carbon, it is necessary to accurately evaluate the effect of quaternary ammonium salt on the binding strength between AC and low-silicon zeolite. However, it is difficult to quantify the binding strength by traditional experimental methods. Therefore, molecular dynamics simulation was used to calculate the interaction mode between them, and the interaction energy and radial distribution function were calculated.
[0124] Model describing the binding process of modified activated carbon and LTA zeolite:
[0125] Since this process mainly occurs at the interface between the modified activated carbon and the LTA zeolite, some simplifications were made during the model construction process. For example, graphene was used to simulate the surface of activated carbon. According to the composition characteristics of activated carbon, some specific functional groups were introduced into graphene to get as close as possible to the chemical properties of the activated carbon surface. At the same time, the LTA zeolite was (110) planarized using Materials Studio software, and then sodium ions were filled into the LTA zeolite framework to balance the charge. The LTA zeolite (110) plane was matched with graphite through cell expansion to construct an activated carbon and zeolite system. Dimethyldiallylammonium chloride (DDA) molecules were added between graphene and zeolite to simulate the interface between the modified and zeolite.
[0126] On this basis, the molecular dynamics simulation of the above model was carried out using LAMMPS software. The simulation was carried out using the reaction force field (ReaxFF), which can describe the interaction of all atoms in the system. First, the activated carbon (AC), dimethyldiallyl ammonium chloride (DDA), LTA zeolite, modified activated carbon (D-AC) system, activated carbon-LTA zeolite (LTA / AC) system, and modified activated carbon-zeolite (LTA / D-AC) system were optimized by structural relaxation at 0K. Then, the formation energy and binding energy of activated carbon and modified activated carbon combined with LTA zeolite were calculated by equations (1) and (2). Then, the molecular dynamics of the modified activated carbon-LTA zeolite (LTA / D-AC) system after structural relaxation in the NPT ensemble was simulated, with a step size of 300K, 1atm, and 0.25fs. The system was first run for 25ps to reach equilibrium, and then for 200ps, with sampling every 1000 steps to obtain the phase space motion trajectory of the system. The calculation formulas for the formation energy and binding energy in the above experimental process are shown in Table 2.
[0127] E f =E AB -E A -E B (1)
[0128] Eb =-E f (2)
[0129] Where E f is the formation energy of A and B to form AB, E b is the binding energy of A and B in AB.
[0130] The interaction energies of activated carbon and modified activated carbon with LTA zeolite are shown in Table 3. It can be seen that the formation energies of activated carbon-LTA zeolite (LTA / AC) system and modified activated carbon-zeolite (LTA / D-AC) system are both negative, and the formation energy of activated carbon and LTA zeolite is -324.97 kcal·mol-1, indicating that activated carbon and LTA zeolite can combine with each other. After adding dimethyldiallylammonium chloride (DDA), the formation energy is significantly reduced from -324.97 kcal·mol-1 to -1076.46 kcal·mol-1, indicating that modified activated carbon is easier to combine with LTA zeolite. The binding energy is opposite to the formation energy, and the binding energy of the modified activated carbon-LTA zeolite system is much higher than that of the AC-LTA zeolite system. The results show that LTA zeolite is strongly combined with modified activated carbon, and the application of the composite material is more stable.
[0131] Table 3 Interaction energy between activated carbon and modified activated carbon and LTA zeolite
[0132]
[0133] On this basis, equilibrium molecular dynamics (EMD) simulations were performed on the modified activated carbon-zeolite (LTA / D-AC) after structural relaxation, describing the binding process between the modified activated carbon and LTA zeolite in the presence of dimethyldiallylammonium chloride (DDA). Then, the average distance between the modified graphene and LTA zeolite at different stages was calculated. The results are shown in Figure 7 .
[0134] like Figure 7 As shown in (a), an obvious displacement of LTA zeolite to the modified graphene can be observed, and the distance between them is from Shorten to The combination of LTA zeolite, dimethyldiallylammonium chloride (DDA) and modified activated carbon (D-AC) becomes close, and the simulation results are basically consistent with the experiments.
[0135] However, there are some differences from the previous analysis, such as the analysis that LTA zeolite and activated carbon (AC) are difficult to combine because they both have negative charges. In the simulation process, since the formation energy of LTA zeolite and activated carbon (AC) is negative, the two can combine by themselves.
[0136] To verify this, unmodified AC and seed crystals were added to the synthesis solution for crystallization. The specific process was roughly the same as Experimental Example 1, except that the modified activated carbon was replaced by activated carbon to obtain a zeolite activated carbon composite material (LTA / AC).
[0137] The microscopic morphology of the product is Figure 7 (b) is shown. Obviously, a small amount of zeolite is loaded on the unmodified activated carbon (AC), which is consistent with the simulation conclusion, but contradicts the conclusion that they have the same negative charge and are difficult to combine due to electrostatic repulsion. The main reason for this contradiction is that the adsorption capacity of activated carbon (AC) is ignored. Since the composite material is prepared by the seed induction method, the adsorption force of some zeolite crystals is greater than the electrostatic repulsion, so that it combines with activated carbon (AC) and then crystallizes to form the composite material. Similarly, due to the electrical neutrality of zeolite crystals, when preparing zeolite activated carbon (ZSM-5 / AC) composite materials, the attraction of activated carbon (AC) to them depends on the adsorption force; in addition, the size of these zeolite crystals is nanometer-sized, and most of them are adsorbed into the pores by AC; these factors lead to a small amount of ZSM-5 zeolite loaded in the prepared composite material. Since the above process cannot be strengthened, it is difficult to improve the problem of poor loading of high silicon and pure silicon zeolites on activated carbon (AC). In summary, a small amount of low-silicon zeolite can be loaded on activated carbon through the seed induction method, but the surface charge modification of activated carbon and the strengthening of the bonding process between seeds and modified activated carbon are effective methods to greatly increase the zeolite loading. The modified activated carbon and zeolite in the prepared composite material are tightly bound and have a strong binding force.
[0138] Performance Testing
[0139] (1) Adsorption performance
[0140] Dichloromethane with strong polarity was used as the adsorbent to evaluate the adsorption performance of the composite material. Specifically, a fixed bed adsorption device was used to evaluate the adsorption performance of the sample for dichloromethane through gas mixing, adsorption, analysis and other steps, and the effect of loaded zeolite on the adsorption capacity of activated carbon was investigated.
[0141] The composite material and activated carbon were placed in a vacuum drying oven at 150° C. for 4 hours, respectively, and then 100 mg was weighed and loaded into a tubular fixed-bed glass reactor (id is 10 mm).
[0142] The raw material gas is dichloromethane standard gas (8.314 g / m 3 ), the gas flow rate was 50 ml / min. The content of dichloromethane in the outlet gas was determined by Agilent 7980A online gas chromatograph GC-flame ionization detector FID.
[0143] The results are as follows Figure 8As shown in (a), the activated carbon adsorbs ethylene dichloride. The penetration time of the activated carbon bed is 20 minutes, while the penetration time of the LTA / D-AC composite bed is close to 40 minutes. This shows that the LTA / D-AC composite can effectively improve its adsorption of dichloromethane.
[0144] At the same time, in order to gain a deeper understanding of the evolution of the pore structure of D-AC and LTA zeolites during the combination process and to clarify the main reasons for the changes in the adsorption performance of the zeolite activated carbon (LTA / D-AC) composite material, its pore structure was characterized, such as Figure 8 (b) as shown.
[0145] Figure 8 (b) shows that the specific surface area of AC is 846.9 m 2 / g, the specific surface area of LTA zeolite is 466.0m2 / g. The specific surface area of zeolite activated carbon (LTA / D-AC) composite material is 519.3m 2 / g, which is between the two. Compared with AC, the specific surface area of the composite material is significantly reduced, which is mainly due to the use of DDA to modify AC to block part of the pores and the loading of a large amount of LTA zeolite on the surface of D-AC. Generally speaking, when the pore structure is negatively affected, the adsorption capacity of the composite material will decrease, and the adsorption curve also proves this point of view. However, the adsorption capacity of the composite material for dichloromethane is better than that of AC. The results confirm that the method of loading zeolite on D-AC to improve its adsorption effect on polar organic matter is feasible.
[0146] (2) Thermal stability
[0147] The thermal stability of activated carbon and LTA / D-AC composites in air atmosphere was evaluated by thermogravimetric analysis. Fig. 9 shown.
[0148] From the TG curve, it can be seen that when the temperature is higher than 650℃, the mass of activated carbon is only 7.8% and the mass loss is 92.2%, which is mainly caused by the oxidation of the carbon matrix in the activated carbon. Under the same conditions, the residual mass of the composite material is 39.4% and the mass loss is 60.6%, which is much lower than that of activated carbon. According to the approximate analysis, it shows that more than 30% of the zeolite is loaded on the activated carbon, which is consistent with the result observed by SEM that a large amount of zeolite is loaded on the surface of the activated carbon. At the same time, from the DTG curve, the mass loss rate of activated carbon is higher than that of the composite material.
[0149] In order to further evaluate the safety of activated carbon and composite materials, the thermogravimetric results were analyzed in depth, and their ignition points were obtained, which were 571°C and 564°C, respectively, with little difference between the two. Obviously, the loading of zeolite did not reduce the ignition point of AC, which still had a high ignition point.
[0150] Example 4
[0151] In the field of industrial-scale VOCs purification, activated carbon is usually formed into a column or honeycomb shape for gas adsorption and purification, especially columnar activated carbon is widely used in printing, paint and other industries. In order to reflect the application value of this application, the commercial columnar activated carbon (not powder) is modified and loaded with zeolite, as follows:
[0152] Test Example 1
[0153] (1) Modification of activated carbon: Weigh 4 g of columnar activated carbon and 200 ml of dimethyldiallylammonium chloride solution (concentration of 5 wt%), mix and shake in a water bath shaker for 3 h at a speed of 160 rpm / min and a reaction temperature of 25°C, then filter and dry in an oven at 80°C for 12 h;
[0154] (2) Wet mixing: weigh 2.73 g of modified columnar activated carbon prepared in step (1), 0.16 g of commercial 5A molecular sieve, 3.85 g of silica sol (SiO2 solid content 30%), 1.64 g of sodium aluminate, 1.73 g of sodium hydroxide, and 19.95 g of deionized water, and mix and shake in a water bath shaker for 1 h at a speed of 160 rpm / min and a reaction temperature of 25°C;
[0155] (3) Aging: After mixing, the wet material is placed in a polytetrafluoroethylene liner and aged at room temperature and pressure for 24 hours;
[0156] (4) Crystallization: After aging, the material is placed in a hydrothermal autoclave and then placed in a constant temperature drying oven for crystallization at 100°C for 6 hours; (5) Drying: The wet material after crystallization is washed with water in sequence until the pH is <8, and then dried at 80°C for 24 hours, and then cooled to obtain a zeolite activated carbon composite material (LTA / modified columnar activated carbon, composite material 1).
[0157] Test Example 2
[0158] The order of addition in step (2) was changed, that is, the commercial LTA zeolite molecular sieve was first dispersed in ethanol, and then the modified activated carbon was added and mixed with the zeolite synthesis liquid after drying. The rest was the same as above, and a zeolite activated carbon composite material (LTA / modified columnar activated carbon, composite material 2) was obtained.
[0159] Performance Analysis
[0160] (1) The morphology of the zeolite activated carbon composite materials (composite material 1 and composite material 2) prepared above was analyzed, and the loading of zeolite molecular sieve on the surface of activated carbon was observed by scanning electron microscopy.
[0161] The specific operation is as follows: the surface morphology of the composite material is analyzed using a Gemini 30 thermal field emission scanning electron microscope from Zeiss, UK, with an accelerating voltage of 2kV and an SE2 probe. The sample needs to be pretreated before the test: the sample is ultrasonically dispersed in an ethanol solution for 30 minutes, then a drop of the sample suspension is added to the copper sheet, dried in an oven at 105°C for 5 minutes, and then the copper sheet is placed on the workbench and observed in a transmission electron microscope. The test results are shown in Fig.10 and Fig.11 .
[0162] like Fig.10 and Fig.11 As shown, it can be seen that the two prepared composite materials have a good loading effect on the surface of the activated carbon. The obtained zeolite molecular sieve crystals have a good morphology and are regular cubic blocks. (2) Nitrogen adsorption and desorption tests were carried out on the original columnar activated carbon and the zeolite activated carbon composite materials prepared by the two methods (composite material 1 and composite material 2).
[0163] The pore structure parameters of AC and its modified samples were determined using a gas adsorption analyzer (ASAP2020 Plus, Micromeritics, USA). Before analysis, these samples were first degassed at 200°C, and the total specific surface area of the samples was calculated using the BET model by measuring the amount of adsorbed and desorbed gas. The test results are shown in Fig.12 .
[0164] like Fig.12 As shown in the figure, the surface area of the composite material tends to decrease slightly compared with the original activated carbon. This is mainly due to the blocking of some pores when the activated carbon is modified with dimethyldiallylammonium chloride, and the large amount of LTA zeolite loaded on the surface of the activated carbon. However, the specific surface area of the original activated carbon and the composite material is not much different, indicating that the LTA zeolite loaded on the surface of the activated carbon will not block the activated carbon pores, and the two do not form a "coated" core-shell structure, which is consistent with Fig.10 and Fig.11 The results observed in .
[0165] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a zeolite activated carbon composite material, characterized in that: The zeolite activated carbon composite material includes modified activated carbon and zeolite; The specific steps include: (1) obtaining modified activated carbon; (2) mixing the modified activated carbon with zeolite synthesis liquid, and crystallizing to obtain the zeolite activated carbon composite material, wherein the amount of the modified activated carbon added is 10-50wt% of the zeolite synthesis liquid; the crystallization conditions are: temperature 80-200°C, time ≥4h, and mixing the modified activated carbon with the zeolite synthesis liquid in the presence of zeolite seed crystals; The modified activated carbon comprises a quaternary ammonium salt and activated carbon; the quaternary ammonium salt is located on the surface of the activated carbon; The zeolite is located on the surface of the modified activated carbon; The quaternary ammonium salt is selected from at least one of the compounds having the structure of formula IV, Formula IV Among them, X - is an ion with a negative charge; R 11 , R 21 Any one independently selected from C1~C4 alkanes, alkenes or alkynes with or without substituents; The mass content of the zeolite in the zeolite activated carbon composite material is ≥20%; The silicon-to-aluminum ratio of the zeolite is ≤15.
2. The preparation method according to claim 1, characterized in that: The isocharge point of the modified activated carbon is ≥7; the mass content of the quaternary ammonium salt in the modified activated carbon is 10%.
3. The preparation method according to claim 1, characterized in that: The quaternary ammonium salt is dimethyldiallylammonium chloride.
4. The preparation method according to claims 1-3, characterized in that: The zeolite synthesis solution comprises a strong alkaline hydroxide or an alkali metal oxide, a silicon source, an aluminum source and water.
5. The preparation method according to claims 1-3, characterized in that: Step (1) comprises: mixing a quaternary ammonium salt solution with activated carbon, reacting the mixture, and obtaining modified activated carbon.
6. The preparation method according to any one of claims 1 to 3, characterized in that: The zeolite seed crystals are dispersed in a solvent, and modified activated carbon is added to obtain a mixture I; and the mixture I is mixed with a zeolite synthesis liquid.
7. Use of the zeolite activated carbon composite material prepared by the method for preparing the zeolite activated carbon composite material according to any one of claims 1 to 6 in a process for adsorbing waste gas and wastewater.
8. The use according to claim 7, characterized in that: Application in adsorption of VOCs.
Citation Information
Patent Citations
Preparation method of diatomite / molecular sieve composite material for adsorbing volatile organic pollutants
CN109304141A
Modified activated carbon as well as preparation method and application thereof
CN115193410A